2013
DOI: 10.1007/s10048-013-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic aspects of PCDH19-related epilepsy syndromes and the possible role of PCDH19 mutations in males with autism spectrum disorders

Abstract: Epilepsy and mental retardation limited to females (EFMR), caused by PCDH19 mutations, has a variable clinical expression that needs further exploration. Onset of epilepsy may be provoked by fever and can resemble Dravet syndrome. Furthermore, transmitting males have no seizures, but are reported to have rigid personalities suggesting possible autism spectrum disorders (ASD). Therefore, this study aimed to determine the phenotypic spectrum associated with PCDH19 mutations in Dravet-like and EFMR female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 32 publications
1
81
2
4
Order By: Relevance
“…The present finding of downregulation of RBFOX1 (Table 2) supports its critical role in controlling the expression of number of genes in epilepsy. It is also interesting to note that mutations observed in PCDH19 PR-gene (van Harssel et al, 2013), calcium dependent cell adhesion protein which is primarily expressed in brain, could have been induced by PRs.…”
Section: Epilepsymentioning
confidence: 97%
See 1 more Smart Citation
“…The present finding of downregulation of RBFOX1 (Table 2) supports its critical role in controlling the expression of number of genes in epilepsy. It is also interesting to note that mutations observed in PCDH19 PR-gene (van Harssel et al, 2013), calcium dependent cell adhesion protein which is primarily expressed in brain, could have been induced by PRs.…”
Section: Epilepsymentioning
confidence: 97%
“…play a possible role in causing intellectual disability and seizure(van Harssel et al, 2013) (van Harssel et al, 2013 and duplication in GRIA3 showed to affect intellectual disability(Wu et al, …”
mentioning
confidence: 98%
“…The key clinical characteristics of this rare epilepsy syndrome are the early onset (mean age 9–10 months6) of fever-associated seizures and prominent seizure clusters 7. Patients develop several different seizure types, most commonly tonic–clonic or tonic, but occasionally atonic and absence seizures.…”
Section: Pcdh19-related Epilepsymentioning
confidence: 99%
“…Eight children (cases 4-11) were diagnosed with Dravet syndrome (previously described 17 ) and had a pathogenic SCN1A mutation. One girl (case 12) had epilepsy and mental retardation restricted to female subjects and a de novo protocadherin 19 (PCDH19) mutation (described as case 7 in van Harssel et al 28 Five of the 8 children had fever-sensitive epilepsy classified as febrile seizures plus (cases 16 and 19-22). In 3 children, a (grand)parent had had febrile seizures as well, consistent with a diagnosis of genetic epilepsy with febrile seizure plus (GEFS+) syndrome.…”
Section: Group Ii: Epileptic Encephalopathymentioning
confidence: 99%